Penilaian Kinerja Keuangan Menggunakan Metode Economic Value Added (Eva) Pada PT United Tractors, Tbk - Winda Anastasya; Mariaty Ibrahim (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
This study aims to analyze the financial performance of PT United Tractors, Tbk using the Economic Value Added (EVA) method. The data analysis technique used in this research is quantitative descriptive analysis. The technique used for data collection is using documentation techniques. The results of the study show that the calculation of Economic Value Added (EVA) at PT United Tractors, Tbk from 2017-2021 produces a positive EVA value or the EVA value produced by PT United Tractors, Tbk is greater than zero (EVA > 0). This shows that the company has generated economic value added. Even though the net profit generated by PT United Tractors, Tbk from 2017-2021 has fluctuated, PT United Tractors, Tbk was able to generate economic value added for the company. This positive EVA value is caused by the NOPAT value which exceeds the cost of capital, so that company management is able to create economic value added for the company and investors, so that it can be said that the financial performance of PT United Tractors, Tbk is in good condition.